Impact of COVID−19 pandemic on neurodevelopmental outcome in very low birth weight infants: a nationwide cohort study - Kim, Hyuna; Jang, Yong Hun; Lee, Joo Young; Lee, Gang Yi; Sung, Jae Yong; Kim, Mi Jung; Lee, Bong Gun; Yang, Seung; Kim, Jinsoo; Yoon, Kyung Seu; Ahn, Ja-Hye; Lee, Hyun Ju (Frontiers in Pediatrics, 2024)
Introduction: Children who have experienced the coronavirus disease 2019 (COVID-19) pandemic are at an increased risk of adverse neurologic developmental outcomes. Limited data exist on the environmental influences of during the COVID-19 pandemic on preterm infant development. This study aimed to investigate whether COVID-19 exposure affects the neurodevelopmental outcomes in preterm children up to 3 years of age. Methods: This prospective cohort study included all very low birth weight (VLBW) infants from the Korean Neonatal Network who had undergone a neurodevelopmental assessment between January 2015, and May 2022. The neurodevelopmental outcomes along with the scores on the Bayley Scales of Infant and Toddler Development (BSID) and the Korean Developmental Screening Test for Infants and Children of pediatric patients aged 18-24 and 33-39 months who were exposed to COVID-19 were compared with those of preterm VLBW children born and tested before the pandemic.3 Results: The cohort included 1,683 VLBW infants. The pandemic group had significantly lower language scores on the BSID-III at ages 18-24 months (p=0.021) and 33-39 months (p=0.023) than the pre-pandemic group after adjusting for gestational age, morbidity, and environmental factors. At 2 nd follow-up period, the pandemic group showed significantly lower scores in the cognitive (p=0.026) domains with a mean difference of 7 points and had a significantly higher percentage of ≤-1SD in the gross motor domain (p<0.001) compared with the pre-pandemic group.Preterm children who experienced the COVID-19 pandemic are at higher risk of abnormal neurodevelopmental outcomes in the first 3 years of life than preterm infants born before the COVID-19 pandemic.